Simultaneously achieved large reversible elastocaloric and magnetocaloric effects and their coupling in a magnetic shape memory alloy. (1st June 2018) - Qu, Y.H.; Cong, D.Y.; Li, S.H.; Gui, W.Y.; Nie, Z.H.; Zhang, M.H.; Ren, Y.; Wang, Y.D.
Abstract: Large reversible caloric effects covering a broad temperature region are essential for high-efficiency and environment-friendly solid-state caloric refrigeration that can potentially replace the traditional vapor-compression-based cooling technology. Here, we report the simultaneously achieved large reversible magnetocaloric and elastocaloric effects in a Ni43 Co6 Mn40 Sn11 magnetic shape memory alloy. A reversible near-room-temperature magnetic entropy change Δ S m of as high as 19.3 J kg −1 K −1 under 5 T was experimentally obtained and the corresponding adiabatic temperature change Δ T ad was estimated to be 7.7 K. Meanwhile, a large reversible elastocaloric effect with a directly measured Δ T ad up to 7.1 K was attained. The elastocaloric effect exhibits high cyclic stability with no apparent degradation during 380 cycles of loading and unloading. Furthermore, we propose and demonstrate the utilization of the multicaloric approach under the coupled uniaxial stress and magnetic field to enlarge the refrigeration temperature region of reversible caloric effects. By combining the reversible magnetocaloric and elastocaloric effects and the reversible multicaloric effect under the coupling of uniaxial stress and magnetic field in the hysteresis region, large reversible caloric effects covering a broad temperature region from 257 K to 383 K can be obtained. This study may pave the way for designing advanced caloric materials with cyclically stable and reversible large caloric effects and wide refrigeration temperature region for solid-state refrigeration. Graphical abstract: Image 1